Effect of High Dose Inhaled Acetic Acid on Airway Responsiveness in Fischer Rats. Issue 5 (3rd October 1998) - Ariel, AP; Furlott, HG; Chapman, KR; Slutsky, AS; Webster, P; Zamel, N; Tarlo, SM
Abstract : BACKGROUND: Sudden, severe airway injury has been associated with an acute, and at times persisting, airway hyper-responsiveness with clinical features of asthma, termed reactive airways dysfunction syndrome (RADS). An attempt was made to develop a rat model of RADS by exposing inbred Fischer rats to inhaled 8 N acetic acid for 2 mins (13 N inhalation was lethal). METHODS: Lung resistance (RL ) and lung elastance (EL ) were measured in 14 eight- to 10-week old male rats. Baseline responsiveness to methacholine was quantified by calculating the dose required for doubling of RL. The next day, the study group (n=11) was exposed to aerosolized acetic acid. Control animals (n=3) were similarly exposed to buffered saline solution. RESULTS: Acetic acid exposure resulted in a significant (P <0.02) increase in RL (by 80%) and EL (by 67%), lasting less than 10 mins postexposure, but no significant change in methacholine responsiveness at one day and seven days postexposure. CONCLUSIONS: Failure to induce persistent airway hyper-responsiveness may relate to the choice of animal, choice of irritant, or insufficient level or duration of exposure, or may reflect a lack of individual predisposing cofactors such as smoking or underlying asthmatic predisposition.